2022
DOI: 10.1107/s2053229622010063
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, and spectroscopic and structural characterization of three new styrylquinoline–benzimidazole hybrids

Abstract: Three new 4-styrylquinoline–benzimidazole hybrids have been synthesized using a reaction sequence in which 2-methylquinoline precursors first undergo selective oxidation by selenium dioxide to form the corresponding 2-formylquinoline intermediates, followed by oxidative cyclocondensation reactions with benzene-1,2-diamine to yield the hybrid products. The formyl intermediates and the hybrid products have all been fully characterized using a combination of IR, 1H and 13C NMR spectroscopy, and high-resolution ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…In each of (IIa)-(IIe), the 2-styryl unit is close to being coplanar with the quinoline unit, while the 4-substituent is twisted well out of the plane of the quinoline unit. These observations thus complement the general pattern in styrylquinolines that we have noted previously (Vera et al, 2022;Ardila et al, 2022). Amongst the styrylquinolines whose structures are recorded in the Cambridge Structural Database (Groom et al, 2016), 2-styryl-and 8-styrylquinolines all have…”
Section: Figuresupporting
confidence: 84%
See 1 more Smart Citation
“…In each of (IIa)-(IIe), the 2-styryl unit is close to being coplanar with the quinoline unit, while the 4-substituent is twisted well out of the plane of the quinoline unit. These observations thus complement the general pattern in styrylquinolines that we have noted previously (Vera et al, 2022;Ardila et al, 2022). Amongst the styrylquinolines whose structures are recorded in the Cambridge Structural Database (Groom et al, 2016), 2-styryl-and 8-styrylquinolines all have…”
Section: Figuresupporting
confidence: 84%
“…The work reported here can be regarded as a continuation of an earlier crystallographic study which reported the structures of 4-styrylquinolines having different substituents at the C2 and C3 positions (Rodrı ´guez et al, 2020;Vera et al, 2022;Ardila et al, 2022).…”
Section: Introductionmentioning
confidence: 55%
“…For each of (IVa)-(IVc), the atom labelling (Figs. 1-3) follows that employed in recent reports on styrylquinoline derivatives (Vera et al, 2022;Ardila et al, 2022). Compounds (IVa) and (IVb) are both triclinic (Table 1), and their corresponding unit-cell repeat distances are fairly similar; however, these compounds are not isomorphous, as the inter-axial angles in (IVa) are all less than 90 � , whereas those in (IVb) are all greater than 90 � .…”
Section: Figurementioning
confidence: 64%
“…All of these type (II) compounds have molecular skeletons in which the styryl and quinoline units are non-coplanar, as reported here for compounds (IVa)-(IVc). This appears to be the case for all of the 4-styrylquinolines which have been structurally characterized so far, in contrast to the 2-and 8-styrylquinolines, where the two ring systems appear always to be effectively coplanar (Vera et al, 2022;Ardila et al, 2022).…”
Section: Figurementioning
confidence: 96%